The impact of the COVID-19 pandemic on the expenditures of hellenic supermarket customers spending clusters: An econometric analysis - Sofia Daskou; Antonis Zairis; Dikaios Tserkezos (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2022)
Purpose: Given the severity and the length of the crisis caused by the COVID-19 pandemic, information on the financial impact of the pandemic becomes useful to enterprises who wish to arm themselves with strategies and policies, designed to combat the effects of similar crises. Such information is particularly useful to grocery retailers, who may need to know the effects of the pandemic on spending behaviour of different spending power classes of consumers. To that end, the study explores the configuration of (supermarket) consumer spending in Greece in relation to the number of: a) reported COVID-19 infections; b) admissions in hospital intensive care units, and: c) number of COVID-19 reported deaths, for the period between February the 26th, 2020 to April 30th, 2021. Design/methodology/approach: Methodologically, the paper focuses on an econometric analysis of daily spending reactions of six distinct spending clusters of consumers of Greek nation -wide supermarket chain, measured against official numbers of COVID-19 related metrics in Greece during the period of February 2020- April 2021. The data used, emerged from daily sales records of a national chain of supermarkets in Greece, consisting of 60 stores. Proven econometric causality techniques were used to analyse the data by applying Hsiao's Optimizing Procedure via the "Stepwise Granger Causality", for the statistical tests of possible interactions between variables. Findings: The study found a phenomenal effect of the number of reported COVID-19 related deaths on consumers' supermarket spending in Greece. The study revealed the statistically significant effects of the COVID-19 variables on the 6 buyers' clusters. These statistically significant effects have a diachronic behaviour which is varied in relation to the covid variables. The findings indicate that the biggest fluctuations in daily consumer reactions (on reported COVID-19 related variables) occurred in lower spending clusters of consumers, diminished over a period of about 15 days. The study also revealed that consumers' spending reaction on infection case is minimal compared to that of reported deaths, signalling a relative apathy to the number of reported infection cases. Research limitations/implications: One basic constraint was the lack of spending data over a longer period of time which would have included the entire pandemic era. Ideally the researchers would prefer to compare customer spending data of several supermarket chains, yet the availability of such data was scarce. The findings also imply that lower spending clusters react more intensively to COVID-19 outcomes and as such marketing efforts to serve these target markets may need to be customized. Originality/value: The interpretation of the results reveals that the level of panic that drives reactionary spending appears to be lower in higher spending consumers. This study contributes to theory by appreciating the Greek supermarket customers' psychological reaction to COVID-19 related variables, by not relying on self-reported data. Although the study was not designed to reveal the reasons for this occurrence, the results demonstrated variability
Keywords: D12; C1; Z1; I1; 330; COVID-19 pandemic; Consumer spending; Grocery Retail Chain; VAR; Granger; Cointegration; Greece